Efficacy of bladder instillations with adelmidrol and sodium hyaluronate for the treatment of symptomatic radiation cystitis - Bracco, Francesco M.; Ammirati, Enrico; Giammò, Alessandro; Gontero, Paolo (Frontiers in Surgery, 2026)
IntroductionRadiation cystitis (RC) is a well–recognized complication of pelvic irradiation, manifesting as symptoms and signs such as hematuria, pain during urination, chronic pelvic pain, urgency and incontinence, which negatively impact patients' quality of life. We conducted a retrospective observational clinical investigation to evaluate the effect of bladder instillation with Adelmidrol (ADM) and sodium hyaluronate (HA) in patients with symptomatic RC.MethodsWe collected data from the patients' clinical records for all patients treated in our hospital with a diagnosis of RC and undergoing a cycle of 8 weekly 60 min bladder instillations with 50 mL a solution of 2% ADM + 0.1% HA. We evaluated the presence of pain (measured with the VAS score), urinary urgency/frequency, macroscopic hematuria and incontinence (all registered as a dichotomous variable present/absent) before and at the end of the treatment.ResultsPelvic pain, evaluated by Visual Analogue Scale (VAS), improved in 66.7% of patients, significantly decreasing from a mean score of 3.8 ± 0.47–1.1 ± 0.3 (p < 0.0001). Gross hematuria and urgency, presented by 83.3% and 90.0% of patients, were reported by 6.7% and 33.3%, respectively, after the end of treatment (p < 0.0001). Incontinence, at first reported by 43.3% of the considered patients, disappeared in 16.7% of the subjects (n.s.).DiscussionThese results suggest the beneficial effect of ADM + HA intravesical instillations in managing RC symptoms, especially pain, gross hematuria and urgency.